Porosité des frontières spatiales, ambiguïté des frontières identitaires : le cas des cités-États swahili de l’archipel de Lamu (vers 1600-1800) - Thomas Vernet (Afriques)
Apprehending, if not defining, Swahili identity is a constant concern of studies dealing with the Muslim communities settled on the shores of precolonial East Africa. Beyond the common – and sometimes redundant – questioning, it seems useful to deepen the analysis of the relationships between the main urban settlements and their mainland hinterland. Based on the case of the Lamu Archipelago ca.1600-1800, this paper aims to enlighten the links between social hierarchy and spatial hierarchy. Surely the Swahili towns were not conceived as open spatial units, yet they kept close relationships of interdependence with the mainland and worked like integrative bodies of great efficiency. Thus, beyond the legitimating discourse spread by the urban elites, it is shown that the porosity and fluidity of the territory of the coastal city-states mirrored the ambiguities of Swahili identity, which permeable and shifting nature should be admitted.